Pengaruh Kepercayaan Konsumen dan kepuasan pada Minat Pembelian Ulang King's Boy Barbershop Surabaya - Erfan Erfan; Triana Setiyarini (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
This research discusses the problems that exist in one of the companies, namely King's Boy Barbershop Surabaya, which is located at Pacuan Kuda, Surabaya No. 46. In this study there are three variables, namely Trust, Customer Satisfaction, and Intention to Revisit. This research uses quantitativeresearchmethods.Thenumberofrespondents was 30 respondents. The purpose of this study was to analyze the influence of customer trust and satisfaction on repeat visit intentions. Using multiple linear regression analysis, the results show that (1) Trust has a positive and significant effect on intention to revisit King's Boy Barbershop; (2) Customer satisfactionhasapositiveandsignificanteffectonintention torevisitKing'sBoy Barbershop Surabaya; (3) Customer Trust and Satisfaction simultaneously influence Revisit Intentions at King's Boy Barbershop Surabaya